2019
DOI: 10.2147/ott.s210939
|View full text |Cite
|
Sign up to set email alerts
|

<p>TNF-like ligand 1A is associated with progression and prognosis of human gastric cancer</p>

Abstract: PurposeThis study aimed to investigate the function of TNF-like ligand 1A (TL1A) in the tumorigenesis and progression of gastric cancer (GC).MethodsRNA-seq gene expression and clinical information for GC patients were obtained from The Cancer Genome Atlas (TCGA) database. Differentially expressed genes (DEGs) between GC tissue samples and normal controls were screened with the edgeR package. Identification of gene co-expression and functional enrichment analyses were performed with Pearson’s correlation analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In addition, Jiang et al (2019) suggested that DPYSL4 is significantly associated with OS in hepatocellular carcinoma. High expression of ISG20 is related to poor clinical outcomes in glioblastoma (Gao et al, 2019). GRM8 is a tumour-suppressor gene in endometrial cancer cell lines (Liang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Jiang et al (2019) suggested that DPYSL4 is significantly associated with OS in hepatocellular carcinoma. High expression of ISG20 is related to poor clinical outcomes in glioblastoma (Gao et al, 2019). GRM8 is a tumour-suppressor gene in endometrial cancer cell lines (Liang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Several key cytokines take a major role in this step, including IL-17A, granulocyte-colony stimulating factor (G-CSF), granulocyte-macrophage colony-stimulating factor (GM-CSF), and TNFa. All these cytokines are largely produced at tumor sites, and their blood levels increase during cancer diseases (48)(49)(50)(51)(52)(53)(54)(55)(56). Concurrent myelopoiesis at the BM and secondary lymphatic organs may allow intensive accumulation of myeloid cells at the tumor site (1,2,14).…”
Section: The Recruitment Of Mdsc At Tumor Sites As a Multistep Event mentioning
confidence: 99%
“…Studies have shown that the TNF family of cytokines and their receptors such as tumor necrosis factor receptor-associated factor 2 and TNF-like ligand 1A are associated with the prognosis of gastric cancer. [ 45 , 46 ] In addition, NOX4 predicts a poor prognosis of gastric cancer patients. [ 47 , 48 ] However, the prognostic values of DUSP1 and LONP1 remain unclear.…”
Section: Discussionmentioning
confidence: 99%